MENGENAL PARIWISATA HALAL DAN PERKEMBANGANNYA DI INDONESIA - Agna Sabrina; Dinda Rizqa Aulia; Shabrina Azzahra; Khairina Tambunan (CV. Barokah Publsiher, 2022)
The tourism sector is a problem related to travel as tourism is carried out due to the strength of the attractiveness of travel in the country. Tourists are a field that makes it possible to build the economy in the country. With the existence of a global halal lifestyle, it has led to halal tourism in countries, especially countries with a majority Muslim population, such as Indonesia. Halal tourism in Indonesia can affect economic growth. Many provinces and tourist destinations carry out halal tourism travel programs, halal tourism has very developed potential in Indonesia. In Islamic law, halal tourism law uses the guidelines of the Qur'an and sunnah. Halal tourism also pays attention to the values of Islamic teachings such as: (1) monotheism (oneness), such as providing mosque facilities; (2) 'adl (justice), Serving tourists in an equal way without bringing elements of SARA; (3) the khilafah (government), by using the method of legal regulation bringing the breath of Islam; (4) nubuwwah (predictions), concern for prophetic morality; and (5) ma'ad(back), implying an economy not only for the world but also for religion. This research aims to compare tourism and the development of Halal tourism in Indonesia and to understand the potential of halal tourism in Indonesia as a tourist destination